THE IMPACT OF USER-GENERATED CONTENT (UGC) ON CUSTOMER ENGAGEMENT AND BRAND LOYALTY - Fadilah Kemala; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
The COVID-19 pandemic has made social media the latest information channel, encouraging firms to use it as a marketing channel. Creating relevant firm-generated content for consumers and social media users is one strategy that can be applied. This study is based on the service-dominant logic theory which aims to develop a conceptual framework involving variables of firm-generated content, customer   engagement,   user-generated   content,   consumer-based  brand   equity,   and  purchase intention.  This  study  has  248  sample  data  and  was  analyzed  quantitatively  using  the  Structural Equation Modelling (SEM) method through the Analysis of Moment Structure (AMOS) version 24 program.  The  findings  of  this  study  show  that  customer  engagement  and  consumer-based  brand engagement  as  mediating  variables  have  strengthened  the  relationship  between  firm-generated content and purchase intention. Specifically, there are significant effects for firm-generated content and  user-generated  content  on  customer  engagement,  user-generated  content and  customer engagement on consumer-based brand equity, and customer engagement and consumer-based brand equity on purchase intention. However, the relationship between customer engagement and purchase intention has proven no significant positive effect, so there is one rejected hypothesis.